Short- and Long-Run Effects of a Sizable Child Subsidy: Evidence from Russia - Ilia Sorvachev; Evgeny Yakovlev (Institute of Labor Economics (IZA), 2020)
This paper utilizes a large-scale natural experiment aimed at increasing fertility in Russia. Motivated by a decade-long decrease in fertility and population, the Russian government introduced a sequence of sizable child subsidies (called Maternity Capitals) in 2007 and 2012. We find that the Maternity Capital resulted in a significant increase in fertility both in the short run and in the long run, and has already resulted in an increase in completed fertility for a large cohort of Russian women. The subsidy is conditional and can be used mainly to buy housing. We find that fertility grew faster in regions with a shortage of housing and with a higher ratio of subsidy to housing prices. We also find that the subsidy has a substantial general equilibrium effect. It affected the housing market and family stability. Finally, we show that this government intervention comes at a substantial cost: the government's willingness to pay for an additional birth induced by the program equals approximately 50,000 dollars.
Keywords: J1; H1; I1; 330; fertility; maternity capital; housing